2012
DOI: 10.1007/s12291-012-0210-2
|View full text |Cite
|
Sign up to set email alerts
|

MMP 9 Gene Promoter Polymorphism in Gastric Cancer

Abstract: Matrix metalloproteinase-9 (gelatinase B) plays a key role in cancer invasion and metastasis by degrading the extracellular matrix and basement membrane barriers. A cytosine (C) > thymidine (T) single nucleotide polymorphism (SNP) at position -1562 in the MMP-9 promoter is reported to influence the expression of the gene. Genotyping of MMP-9 -1562 C→T promoter polymorphism in 140 gastric cancer patients and 132 healthy control subjects was carried out in order to evaluate its association with progression and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In the present study, the frequencies of MMP‐2 ‐735C > T polymorphisms of healthy controls were comparable with those from a previous study in North India, although they differed from those of another study in North India . The frequencies of the MMP‐9 ‐1562C > T polymorphism of healthy controls were comparable with a North Indian study and differed from those in a South Indiam study …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the present study, the frequencies of MMP‐2 ‐735C > T polymorphisms of healthy controls were comparable with those from a previous study in North India, although they differed from those of another study in North India . The frequencies of the MMP‐9 ‐1562C > T polymorphism of healthy controls were comparable with a North Indian study and differed from those in a South Indiam study …”
Section: Discussionsupporting
confidence: 77%
“…32 The frequencies of the MMP-9-1562C > T polymorphism of healthy controls were comparable with a North Indian study 33 and differed from those in a South Indiam study. 34 In the present study, individuals with CT genotypes and the T allele of MMP-2 had a reduced risk of severe HAND. A C > T transition of the -735C/T polymorphism disrupts the core recognition sequence of the Sp1 site (CCACC box), which displays lower promoter activity for the T allele.…”
Section: Discussionsupporting
confidence: 47%
“…The T allele of MMP9 -1562 is associated with elevated MMP-9 plasma concentration [32] in accordance with the increased promoter activity of the -1562T allele [33]. As a result, MMP9 C-1562T is associated with susceptibility to GC [34]. On the other hand, MMP9 R668Q is located in the hemopexin-like domain, which is necessary for the collagenase activity of MMP-9 [35], and is associated with survival in lung cancer [36] and melanoma [37].…”
Section: Discussionmentioning
confidence: 92%
“…In addition, these Chinese researchers [ 4 ] found that the genotype of MMP-9 is correlated with TNM classification and lymph node metastasis and plays an important role in the progression and metastasis of gastric cancer. In contrast to the abovementioned investigation, two additional studies published by Chinese researchers [ 6 , 7 ], one additional study published by Indian researchers [ 8 ], and one study published by Turkish researchers [ 9 ] suggest no relevant association of MMP-9 with gastric cancer. Therefore, we conducted this meta-analysis to verify the association of MMP-9 SNPs with the risk of GC.…”
Section: Introductionmentioning
confidence: 78%
“…The best possible score of this scale is 9 points. In this meta-analysis, two studies [ 3 , 13 ] scored 8 points; six studies [ 4 – 6 , 8 , 9 , 14 ] scored 7 points; and one study [ 7 ] scored 6 points.…”
Section: Resultsmentioning
confidence: 99%